Femme fatale or damsel in distress? acomparative study of female antagonists in ABS-CBN teleseryes - Lagrosa, Anna Angela A. (2013)
"The portrayal of contemporary female antagonists in ABS-CBN teleseryes has adapted into increasingly bold, daring, and sexy women, defying the traditional constructs of femininity. However, as female characters, first and foremost, albeit antagonists, they were still subject to the constraints of patriarchy. This undergraduate thesis used Laura Mulvey's theory of the Male Gaze and Visual Pleasure as well as Gender Representation, to conduct a comparative textual analysis of the depiction of female antagonists in Rubi, Mara Clara and Nasaan Ka, Elisa? The researcher evaluated the personalities, experiences, motivations, relationships, and actions of the different female antagonists from the respective shows, and came to the conclusion that female antagonists from the respective shows, and came to the conclusion that female antagonists, as with all female characters, remained oppressed, struggling against their circumstances, victims and victimizers of each other. Moreover, they suffered the wrath of patriarchy twofold, because they were treated as sec objects, lovely to behold, and thus stimulating the reaction of visual please, while masking the fear from the castration complex. They were subsequently ruined in similar fashion, permanently scarred and subdued, or disfigured in death, strengthening the discourse of patriarchy. The researcher recommends further study and wider comparison with more teleseryes and audience studies to determine the response of viewers to the female antagonists and validate the textual analysis from without."